Well‐differentiated thyroid cancer with aerodigestive tract invasion: Long‐term control and functional outcomes. Issue 1 (6th April 2015) - Su, Shirley Y.; Milas, Zvonimir L.; Bhatt, Neel; Roberts, Dianna; Clayman, Gary L.
ABSTRACT: Background: Well‐differentiated thyroid cancer (WDTC) invading the aerodigestive tract is an uncommon entity associated with significant morbidity and reduced survival. Methods: We reviewed the surgical treatment, oncologic control, and functional outcomes of 69 consecutive patients with WDTC invading the upper aerodigestive tract. Results: Complete tumor excision with negative margins was achieved in 62% of patients. Tracheostomy dependence (27%) and permanent hypoparathyroidism (49%) were present or the result of surgery. Seventy‐one percent of patients ate a regular diet, 59% had normal speech, and the majority (62%) reported normal activities of daily living. The local, regional, and distant recurrence was 1%, 14%, and 23%, respectively. The 5‐year overall survival (OS) and disease‐free survival (DFS) was 71% and 45%, respectively. Conclusion: Surgical resection and appropriate adjuvant treatment can achieve excellent locoregional control while preserving function and quality of life. Long‐term survival is limited by the high incidence of distant metastasis. © 2015 Wiley Periodicals, Inc. Head Neck 38: 72–78, 2016